Reactualization of the Ideology of Pancasila in the Globalization - Suko Wiyono; Wahyu Hindiawati; Zulfikar Ramadhan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pancasila as an Open Ideology carries the meaning that it is capable of adapting to the changing times. The fundamental values of Pancasila, which are inherent in the Pancasila ideology, must be firmly held and cannot be altered. The openness pertains to the implementation's elaboration, which can be adjusted to the needs and real challenges faced by the Indonesian nation in each period. This study aims to understand the development of the Pancasila ideology in the era of globalization. The method used in this research is normative juridical research. The results of the study show that globalization cannot be avoided, but the Indonesian nation must take action, establish a determination to build independence with the spirit of modernization in the global era, while still adhering firmly to the Pancasila ideology.